2019
DOI: 10.1039/c9ra08854g
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric exponential amplification reaction-based DNA nanomachine for the fluorescent detection of nucleic acids

Abstract: This label-free and ultra-low background signal DNA nanomachine was based on P-HP mediated S-EXPAR and the G-triplex/ThT complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…These experiments suggested that the sensor molecules behave uniformly. Interestingly, when the experiment in Figure 2 was repeated after injection of a target (p53 tumor suppressor gene: 5′-TTCCTCTGTGCGCCGGTCTCTCCT) 37,49,50 and incubated for ∼20 min, we observed a very different behavior of sensor molecules. In the presence of the target, sensor molecules showed very clear dynamics of Cy3 and Cy5 fluorescence intensities that were anticorrelated.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…These experiments suggested that the sensor molecules behave uniformly. Interestingly, when the experiment in Figure 2 was repeated after injection of a target (p53 tumor suppressor gene: 5′-TTCCTCTGTGCGCCGGTCTCTCCT) 37,49,50 and incubated for ∼20 min, we observed a very different behavior of sensor molecules. In the presence of the target, sensor molecules showed very clear dynamics of Cy3 and Cy5 fluorescence intensities that were anticorrelated.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Another advancement came from Yan et al , who constructed a novel multifunctional hairpin probe (P-HP) incorporating palindromic fragments for a symmetric EXPAR (S-EXPAR) method. 128 This design significantly reduces nonspecific amplification in the EXPAR. Similarly, Kim et al developed a target-inducible strand amplification reaction for detecting target microRNAs (miRNAs) by employing cleverly designed, interrelated reaction pathways 129 (Table 1).…”
Section: Expar-based Assays Incorporating Other Methodsmentioning
confidence: 99%